(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
On November 16-17, 2023, the International Scientific Conference "Geophysical Processes on the Earth and Its Environments" was held at the Ivane Javakhishvili Tbilisi State University, dedicated to the 90th anniversary of the Mikhail Nodia Institute of Geophysics. The conference was organized by TSU, the Institute of Geophysics and the Geophysical Association of Georgia.